Highly regioselective bioconversion of ginsenoside Re into 20(S/R)-Rf2 by an optimized culture of Cordyceps sinensis - Wang, Weinan; Liu, Jishuang; Xin, Yu; He, Tianzhu; Qiu, Ye; Qu, Mo; Song, Yan; Qiu, Zhidong (New journal of chemistry, 2020)
The hydroxylation of C25 on dammarane ginsenosides profoundly influences their therapeutic effect. The resulting 25-OH derivatives have been proven to be more efficacious than their original forms against many diseases. However, this type of ginsenoside is scarce in nature, which hinders their further applications. Furthermore, current strategies for their chemical modification always result in undesirable side products. Nevertheless, although biocatalysis may be suitable for this task, to date, there has been no reports in the literature on this subject. Herein, ginsenoside Re was thoroughly converted into 20(S/R)-Rg2 and their 25-OH derivatives 20(S/R)-Rf2 using Cordyceps sinensis in an optimized medium composed of 20 g L −1 glucose, 5 g L −1 ammonium sulfate, and 1 mM FeCl 3 . The chemical correctness of both ginsenoside Rf2 enantiomers was validated via LC-IT-TOF-MSn and 13 C-NMR methods. Time-course experiments indicated reaction equilibrium after 6 days of biocatalysis. The transformation pathway was established to be Re → 20(S/R)-Rg2 → 20(S/R)-Rf2. The absolute quantity for both enantiomers of Rf2 was determined by multiple reaction monitoring modes of LC-QQQ-MS and their molar bioconversion rate was calculated to be 83.1%, of which 20(S)-Rf2 accounted for 46.8%, while 20(R)-Rf2 36.3%. These two 25-OH derivatives are the direct hydration products from 20(S/R)-Rg2 with no other side metabolites, suggesting that this is a highly regioselective catalytic system. Owing to the high yield of the target compound and simple chemical background in the reaction mixture, this biocatalytic system can be employed for the facile preparation of several 25-OH ginsenosides.